Morphometric examination of glandula lacrimalis of Hamdani sheep by computed tomography - Güzel, Barış Can; Demircioğlu, İsmail (Kastamonu Üniversitesi, 2022)
This study was carried out to obtain morphometric measurements of glandula lacrimalis of Hamdani sheep on computed tomography (CT) images and to determine the biometric differences of these measurement values in terms of both homotypic variations and sexual dimorphism. In the study, CT images of glandula lacrimalis obtained from 10 adult healthy Hamdani sheep, containing five males and five females were used. Morphometric measurements were taken from the transversal, sagittal and dorsal sections of the right and left glandula lacrimalis. Statistical analysis was performed for morphometric values. In the morphometric examinations, the mean length, width, and height values for both the right and left glandula lacrimalis were found to be 15.71 ± 0.17 mm, 9.39 ± 0.9 mm, 4.84 ± 0.5 mm, respectively, for male Hamdani sheep; in females, these values were determined as 13.80 ± 0.37 mm, 8.40 ± 0.5 mm and 4.14 ± 0.67 mm, respectively. As a result, statistical gender differences in the measurement parameters of glandula lacrimalis of adult Hamdani sheep were determined using computed tomography images.
Keywords: Veterinary Surgery; Veteriner Cerrahi